Ocular manifestation in patients with HIV/AIDS: a hospital-based retrospective study. Issue 1 (October 2019) - Li, Wangting; Wang, Xiaoli; Zhao, Lanqin; Lin, Duoru; Liu, Zhenzhen; Wu, Xiaohang; Wang, Jinghui; Zhang, Xiayin; Yang, Yahan; Wang, Ruixin; Li, Ruiyang; Huang, Wenyong; et al.
Abstract: Background: Ocular manifestation, which occurs in 82·6% patients with HIV/AIDS, affects quality of life and has become a serious global public health problem. However, little attention has been paid to this issue because of its uncertain relationship with survival outcome. We aimed to demonstrate the potential relationship between ocular manifestation and the activity of general diseases in patients with HIV/AIDS, discover the trends and related factors of HIV/AIDS ocular manifestation, and make suggestions to ophthalmic patients with HIV/AIDS. Methods: We retrospectively enrolled patients with HIV/AIDS admitted to Guangzhou Hospital for Infectious Diseases between Jan 1, 2005, and Dec 31, 2016. We collected their HIV/AIDS-related clinical data, hospitalisation information, and demographics. We classified patients into three groups according to the different ophthalmic diagnostic mode they received: non-professional inspection group (2005–11, patients were treated by infectious disease physicians alone without eye examination or the necessary equipment); on-demand inspection group (2012–13, infectious disease physicians decided whether to order an ophthalmology consultation according to the patient's condition); and routine examination group (2014–16, every hospitalised patient with HIV/AIDS had to undergo an ophthalmic examination). Findings: 8743 hospitalised patients with HIV/AIDS (15 116 cases) were enrolled, including 667 (8%) patients diagnosed with ocular diseases. Ocular disease was detected in 65 (2%) of 2902 patients in the non-professional inspection group, 46 (2%) of 1621 in the on-demand inspection group, and 556 (13%) of 3553 in the routine examination group. Infectious disease (354 [53%] of 667 patients) was the main type of ocular manifestation in HIV/AIDS. Most infections occurred in the cornea and conjunctiva (152 [43%] of 354 patients) and retina (145 [41%] of 354 patients). Retinopathy (β=2·392, p=0·007) and retinitis (β=3·562, p<0·001) were positively correlated with CD4-positive counts of less than 200 cells per μL. Among all the hospitalisation and demographic parameters, the ophthalmic examination mode (β=9·427, p<0·001) was the strongest factor for detecting ocular disease, followed by paying by medical insurance, hospitalisation times, average hospitalisation duration, and increasing age. Interpretation: Ocular manifestation in patients with HIV/AIDS is closely related to immune function and nutritional status. Routine ophthalmic examination is the most important factor associated with the detection rate of ocular diseases. Thus, ophthalmic examination should be done on every patient with HIV/AIDS. For patients diagnosed with retinopathy or retinitis, immune system function examination (such as CD4-positive T cell count) is necessary. Funding: National Key Research and Development Program of China (2018YFC011650), Major Research Plan of the National Natural Science Foundation of China, (91846109) and the National Natural Science Foundation of China (81770967).